An investigation into voluntary employee turnover and retention factors in sport organizations - Rissanen, Amanda (2017)
In the past few decades, sport organizations have undergone a major change in their management practices as they are expected to become more and more formal and professional-like. Despite this pressure, human resource managers should give more attention to the retention function in human resource management systems. As employees are the lifeline of sport organizations, much emphasis should be placed on preventing their voluntary turnover. Utilizing qualitative and inductive grounded theory building methods this study aims to provide invaluable information to sport managers about why employees leave or remain in sport organizations. Given the scant research on turnover and retention in sport organizations, this study addresses the questions: “What factors influence voluntary employee turnover intentions in swimming clubs, and what are the top factors that drive employee retention in such sport organizations?” Data were collected via semistructured interviews with eleven instructors of a local swimming club. The data analysis produced two models, one indicating the possible reasons for voluntary turnover in sport organizations, and the other possible retention factors in those organizations. The findings suggest that a challenging job, unsatisfying work environment, and an unrewarding job were amongst the common reasons for intended turnover of key employees. In contrast, a good person-job fit, well-managed organization, and value of the job were some of the factors that were thought to enhance employee retention. The findings of this study are discussed in the context of extant literature and implications for management practice and future research are described. All in all, the findings of this current study increase understanding about the turnover intentions and retention practices in sport organizations.